5+6(x-2)+3=4x

Simple and best practice solution for 5+6(x-2)+3=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6(x-2)+3=4x equation:


Simplifying
5 + 6(x + -2) + 3 = 4x

Reorder the terms:
5 + 6(-2 + x) + 3 = 4x
5 + (-2 * 6 + x * 6) + 3 = 4x
5 + (-12 + 6x) + 3 = 4x

Reorder the terms:
5 + -12 + 3 + 6x = 4x

Combine like terms: 5 + -12 = -7
-7 + 3 + 6x = 4x

Combine like terms: -7 + 3 = -4
-4 + 6x = 4x

Solving
-4 + 6x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-4 + 6x + -4x = 4x + -4x

Combine like terms: 6x + -4x = 2x
-4 + 2x = 4x + -4x

Combine like terms: 4x + -4x = 0
-4 + 2x = 0

Add '4' to each side of the equation.
-4 + 4 + 2x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = 0 + 4
2x = 0 + 4

Combine like terms: 0 + 4 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 7z+2z=z+9 | | cos(x)=12/22 | | 8y=-14 | | 60inch=ft | | 12c=pt | | -3(y+1)-11=-6(y+4)+3y | | 2(n+8)+1= | | (17-y)-2(21+y)= | | 7m-16*2=2m+4 | | 3(x-1)-4(2-X)=3x+1 | | -7m=m+4 | | 15n^2+41n+14=0 | | (2x-5)(4x+7-2)(x-5)= | | s(t)=-16t^2+48t+19 | | 5=3x+5+6 | | (25-2x)(15-2x)=225 | | 8x-(2+5)= | | -2(x+3)=x-3 | | 3t^(1/2)=4 | | 17u-24=10 | | cos=14/25 | | x/15=83 | | -3w-2=-14 | | 50x+20y=450 | | -87+6x=33 | | -7x-2.8=6x-3.2 | | 8x-2x+x=-5 | | 2x=l-3p | | ×/3-9=1 | | 0.254c-4.331=56.456c | | K+6=J | | x-8.82=3.26 |

Equations solver categories